Večmodalna analiza povezav med črevesno mikrobioto, življenjskim slogom in osebnostjo pri nosečnostni sladkorni bolezni - Basar, Ivana (Informatica Medica Slovenica, 2024)
tract. Gut microbiota is primarily influenced by environmental factors and physiological states, including pregnancy. Gestational diabetes mellitus (GDM), the most prevalent metabolic complication in pregnancy, often requires rapid lifestyle adaptation, a process potentially modulated by individual personality traits. This study investigated interrelationships across three data modalities: gut microbiota profiles at the phylum level, lifestyle factors, such as diet and physical activity, and personality traits in women diagnosed with GDM. Stool samples from 21 participants were processed for microbial taxonomic analysis. Behavioral and psychological variables were measured using the Food Frequency Questionnaire, Well-Being Questionnaire, and the PERSONA test. Partial least squares regression was employed to model cross-modality associations. Correlation structures were visualized and interpreted using bipartite network representations.
Keywords: črevesna mikrobiota; gestational diabetes mellitus; gut microbiota; lifestyle; multimodal analysis; nosečnostna sladkorna bolezen; osebnostne lastnosti; personality traits; večmodalna analiza; življenjski slog